Karakteristik Usus Halus Ayam Pedaging yang Diberikan Asam Jeruk Nipis dalam Pakan (SMALL INTESTINE PROFILES OF BROILERS FED WITH LIME TOTAL ACIDS) - Menggi Emma, Wahidin Mardiono Swantho; Sjofjan, Osfar; Widodo, Eko; ., Achmanu (Jurnal Veteriner; Vol 14 No 1 (2013), 2013)
The purpose of this study  was to find out the effect of lime total acids  on the characteristics ofintestine broiler base on its pH, digestive  viscosity, and the number and hight of small intestineof villi. Atotal of120 male Lohmann broiler chicks with the average body weight of 45.29 ± 1.76g, were used in thisstudy which were then allotted into six groups. The six treatment groups consist of : animals feed with noadditional acid (PO) as negative control, animals feed with addition of  0.4% (w/w) commercial citric acid(P1) as positive control, and animals feed with additional of 0.2% (P2), 0.4% (P3), 0.6% (P4), and 0.8% (P5)total acids extracted from lime, respectively.   This study was carried out using Completely RandomizedDesign with four replications.  The results showed that lime total acids had a very significant effect(P<0.01) on the  pH and digestive viscosity.  However, no significant effect (P>0.05) was found on thenumber and height of the villi. The addition of 0.8% total acid on the animals fed give the best result on theintestinal characteristics compared to other treatments.
Keywords: lime total acids, intestinal characteristics, acidifier and broiler